Musculoskeletal care pathways for adults with hip and knee pain referred for specialist opinion: a systematic review. Issue 9 (4th September 2019) - Button, Kate; Morgan, Fiona; Weightman, Alison Lesley; Jones, Stephen
Abstract : Objective: Musculoskeletal care pathways are variable and inconsistent. The aim of this systematic review was to evaluate the evidence for the clinical and/or cost effectiveness of current care pathways for adults with hip and/or knee pain referred for specialist opinion. Design: Systematic review. Data sources: Electronic database searches were carried out in MEDLINE, MEDLINE In-Process, Cumulative Index of Nursing and Allied Health Literature, Embase, PEDro, PubMed, Web of Science, Cochrane Central and Health Management Information Consortium without language restriction from 1990 onwards. Websites were reviewed for grey literature. Eligibility criteria: All study designs and documents that considered care pathways for adults with musculoskeletal hip and/or knee pain referred for specialist opinion were screened by two reviewers. Risk of bias was assessed using The Critical Appraisal Skills Programme checklist for randomised controlled trials and the Joanna Briggs Institute checklists. Data extraction and synthesis: Data extraction and quality assessment were performed by one reviewer and checked by a second. Findings are reported narratively. Results: The titles and abstracts of 1248 articles were screened and 140 full-text articles retrieved. 19 papers reporting 17 studies met the study inclusion criteria. Quality was low due to study design and methodological flaws. Most of the outcomes relate to organisational process at the 'meso' level of a whole systems approach. Conclusion: It can be concluded that the pathway is not linear, containing variations and activity loops. The available evidence suggests that, from the point of referral for specialist opinion, a model is required that integrates the skills of all the different healthcare professionals and streamlining is required to ensure that individuals are seen by the healthcare professional that best meets their needs. There is very limited evidence of patient experience informing knee and hip care pathways. PROSPERO registration number: CRD42016035510.